The Effect of Orally -Administered Calcium Carbonate to Pregnant Women with Mild Pre-eclampsia - Sagban, Sura; N. Al-Shawi, Nada; Mohammad, Alia; Talib, Ashwak; Hasson, Utoor (Iraqi Journal of Pharmaceutical Sciences, 2017)
Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Its exact etiology is not known, although several evidences indicate that various elements might play an important role in pre-eclampsia. This study was carried out to analyze and to compare the concentration of calcium, in mild pre-eclampsia and in normal pregnant women , and to determine the effect of oral supplementation with calcium on mild pre-eclampsia , and whether this effect is related to the change in the level of serum calcium. Forty- five women in the third trimester of pregnancy were selected to participate in this study and divided into: fifteen apparently healthy, normotensive pregnant women served as a control group; thirty clinically diagnosed patients with mild pre-eclampsia ( 15 mild pre-eclamptic un-treated group , 15 mild pre-eclamptic treated with calcium carbonate 500 mg twice daily) , the serum calcium were estimated with an atomic absorption spectrophotometer .the data were analyzed using the un- paired Student’s-test.The serum calcium in mild pre-eclmpatic un-treated group was significantly lower than that in normal pregnant women (8.84 ± 1.14 Vs. 9.66 ± 0.87 , p<0.05) , Serum calcium level significantly increased in mild pre-eclamptic treated with calcium carbonate 500mg twice daily as compared to mild pre-eclamptic un-treated group (9.76 ±0.96 Vs 8.84±1.14 ,p<0.05) . Systolic ,diastolic, and mean arterial blood pressure were significantly reduced after one month of treatment with calcium carbonate 500 mg twice daily as compared to mild pre-eclamptic un –treated group.(134.83 ± 7.5 Vs139.33 ± 5.30, 88.46 ± 3.27 Vs 91 ± 3.38, 103.90 ± 3.8Vs106.66 ± 3.08 ,p<0.05) respectively.This study showed that serum calcium level in mild pre-eclampsia are lower than in normotensive pregnant women ,this finding support the hypothesis that hypocalcemia is a possible etiology in pre-eclampsia ; additionally this study showed the possible beneficial effect of calcium supplementation in controlling pre-eclampsia and reducing blood pressure by increasing serum calcium level . Key words: Mild Pre-eclampsia, Calcium carbonate tablet, Pregnant women, Serum calcium